Pengembangan Digital Dictionary Untuk Mengukur Retensi Mahasiswa Pendidikan Guru Madrasah Ibtidaiyah (PGMI) - Vannisa Aviana Melinda; Dian Eka Aprilia Fitria Ningrum (Universitas Negeri Malang in collaboration with APSTPI and IPTPI, 2020)
The purpose of this research is to produce a digital dictionary and to know the increase in student retention by using digital dictionary. The research is an R&D using a learning Media development model by Lee and Owens, because in this development model has complete flows such as analysis and assessment stages, design stage, development stage, implementation phase, and evaluation phase. The overall validation result of material experts on the digital Media dictionary developed is 92.30% with valid categories. Media expert validation result of the developed digital media dictionary which is 91.67% with valid category. In this study, the bonded variables used were the power of the retention (retention rate) of students against the biological terms contained in the subject matter of plants, animals and humans. In this study, data on student retention rate in 2 weeks was still classified as B (good) with a score of 78.46. Thus, digital media dictionary can increase the ability of student’s retention.